Policy Gaps with Bangladesh Compared to a Few Asian Economies along the Linear Stages Growth Path - Akanda, M. Aminul Islam (International Journal of Economics and Financial Issues, 2022)
This study evaluated growth experiences and identified policy gaps with Bangladesh compared to a few advanced Asian countries. It used secondary data over 120 years in retrospect along with projection to some extent. Whether would Bangladesh be able to enter into subsequent stages along linear stages growth model was a major research question. Bangladesh entered into the third of five stages in the early 1990s. On the other hand, Malaysia reached at the fourth and South Korea at the fifth stage. Bangladesh was too envisioned to reach at peak within 20 years with creative industries and demographic dividend. Some industrial conglomerates and new industries were expanded here in the 2000s. This economy would soon enter into fourth stage satisfying stage-specific indicators like two other economies. It had some policy gaps identified through comparison of stage-specific policies and strategies with others. However, its government, in the second perspective plan (2021-2041), emphasized on ICT based product-innovation and job creation in industry 4.0. Major challenges to moving forward in here was to reducing gaps between planned and actual development.